2017
DOI: 10.1021/acs.organomet.7b00665
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Silicon Triple Bonds: Access to [Si(η5-C5Me5)]+ from SiX2(NHC) and its Conversion to the Silylidyne Complex [TpMe(CO)2MoSi(η3-C5Me5)] (TpMe = κ3-N,N′,N″-hydridotris(3,5-dimethyl-1-pyrazolyl)borate)

Abstract: A novel method to prepare SiCp* 2 (1) (Cp* = C 5 Me 5 ) is presented involving the reaction of N-heterocyclic carbene (NHC)-stabilized Si II halides SiX 2 (NHC) (X = Cl, Br) with 2 equiv of KCp*. This route is a superior alternative to the laborious, multistep synthesis of 1 presently known and provides via the selective protonolysis of 2) in multigram scale and high yield. Reaction of 2 with the tailored metallate Na[Tp Me Mo(CO) 2 (PMe 3 )] afforded the unprecedented silylidyne complex [Tp Me (CO) 2 MoSi(η 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 112 publications
0
26
0
2
Order By: Relevance
“…While the reactions of 1 b with phosphorus(III) and arsenic(III) chloride and ‐bromide only led to complex mixtures of products, the reactions with germanium(II) chloride dioxane adduct, tin(II) chloride and lead(II) chloride as well as antimony(III) chloride gave the corresponding ansa ‐metallocenes 2 b – d and 3 a in excellent isolated yields ( 2 b : 81 %; 2 c : 81 %; 2 d : 84 %; 3 a : 79 %) (Scheme ). Inspired by the report of an alternative synthesis of Jutzi's decamethylsilicocene by Filippou and co‐workers, we employed the potassium salt 1 c in the reaction with IDip⋅SiCl 2 (IDip= N , N ′‐bis(2,6‐diisopropylphenyl)imidazol‐2‐ylidene) to gain access to the related silicocenophane, 2 a . The reaction proceeds smoothly to give 2 a in moderate spectroscopic yield as manifest in the appearance of a new 29 Si NMR signal at δ =−268.2 although we did not yet succeed in the separation of 2 a from the concomitantly liberated IDip and side‐product 1 a .…”
Section: Methodsmentioning
confidence: 99%
“…While the reactions of 1 b with phosphorus(III) and arsenic(III) chloride and ‐bromide only led to complex mixtures of products, the reactions with germanium(II) chloride dioxane adduct, tin(II) chloride and lead(II) chloride as well as antimony(III) chloride gave the corresponding ansa ‐metallocenes 2 b – d and 3 a in excellent isolated yields ( 2 b : 81 %; 2 c : 81 %; 2 d : 84 %; 3 a : 79 %) (Scheme ). Inspired by the report of an alternative synthesis of Jutzi's decamethylsilicocene by Filippou and co‐workers, we employed the potassium salt 1 c in the reaction with IDip⋅SiCl 2 (IDip= N , N ′‐bis(2,6‐diisopropylphenyl)imidazol‐2‐ylidene) to gain access to the related silicocenophane, 2 a . The reaction proceeds smoothly to give 2 a in moderate spectroscopic yield as manifest in the appearance of a new 29 Si NMR signal at δ =−268.2 although we did not yet succeed in the separation of 2 a from the concomitantly liberated IDip and side‐product 1 a .…”
Section: Methodsmentioning
confidence: 99%
“…While for the heavy group 14 elements like germanium, tin and lead, the necessary dichlorides are stable and commercially available compounds, this is not the case for silicon dichloride. Therefore, in the synthesis of silicocenophane, 6 , a dichloro‐silylene carbene adduct was used as the silicon(II) precursor, [57] following a report about the analogues synthesis of decamethyl silicocene by Filippou et al [67] …”
Section: Metallocenophanes Of Group 14 Elements: Tetrelocenophanesmentioning
confidence: 99%
“…While for the heavy group 14 elements like germanium, tin and lead, the necessary dichlorides are stable andc ommercially available compounds, this is not the case for silicon dichloride. Therefore, in thes ynthesis of silicocenophane, 6,adichloro-silylene carbene adduct was used as the silicon(II) precursor, [57] following ar eport about the analogues synthesis of decamethyl silicoceneb yF ilippou et al [67] Furthermore, in 1994 Tacke reported that C [2]stannocenephane 8d and C [2]plumbocenophane 9b can be obtained by the reactiono ft he correspondingm etal with 6,6-dimethylfulvene (Scheme 12), [63] similar to the synthesis of C [2]calcocenophanes 2c-o and C[2]strontiocenophane 3 (vide supra).…”
Section: Metallocenophanes Of Group 14 Elements: Tetrelocenophanesmentioning
confidence: 99%
“…The main exception to this is the chemistry of I , which the Jutzi group has investigated since its synthesis. The primary focus of this has been use of I as a synthon in preparing asymmetric silylenes with a variety of other substituents but also includes other interesting chemistry which has recently been expanded upon by Filippou and coworkers with the synthesis of compound XVI containing a Si−Mo bond with multiple bonding character. Sample reactivity of I is shown in Scheme , and the results to‐date were well‐reviewed by Jutzi himself in 2014 …”
Section: Introductionmentioning
confidence: 99%